Registration Reform and the Role of Political Connections in the Initial Public Offering Process: Evidence From China - Wu, Xihao; Zhou, Qing (Frontiers in Psychology, 2022)
Registration system reform is a significant and important event in the marketization of the Chinese stock market. Using social network theory, we examine how this institutional change affects the function of the network in initial public offering (IPO) activities. The results show that the enterprise’s political connections have a positive impact on IPO approval. However, registration system reform mitigates the role of political connections in IPO approval. In particular, attenuation of the efficiency of political connections under the registration system mainly exists in older firms that have long relationships with the government. The registration system can weaken the positive impact of political connections on IPO approval, even under high economic policy uncertainty where endorsements by the government are most effective. Furthermore, under the current Chinese double-track system, which includes both an approval system and a registration system, we find that enterprises with political connections are more likely to stay in the approval system than to go public in the multiple application rounds, while enterprises that are not politically connected are more likely to switch the issuance system used from the approval system to the registration system. Lastly, we find that intermediate business connections, as an alternative network, can significantly improve the probability of their clients’ IPO approval, and that registration system reform has strengthened the function of intermediate business connections in IPO approval.